2014
DOI: 10.1016/j.jfineco.2014.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Performance evaluation with high moments and disaster risk

Abstract: Traditional performance evaluation measures do not account for tail events and rare disasters. To address this issue, we reinterpret the riskiness measures of Aumann and Serrano (2008) and Foster and Hart (2009) as performance indices. We derive the moment properties of these indices and their sensitivity to rare disasters and show that they are consistent with the asset pricing literature. As applications, we show that "anomalous" investment strategies such as "momentum" or investment in private equity lose m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(30 citation statements)
references
References 52 publications
1
27
0
Order By: Relevance
“…After standardization, however, only the expected shortfall of the German market portfolio remains higher than that of its UMD counterpart. Overall, our statistics presented here are consistent with those reported by Daniel and Moskowitz (2014) and Kadan and Liu (2014), who also found that momentum tends to suffer from severe left-tail risks.…”
Section: Summary Statistics: First and Secondsupporting
confidence: 92%
See 1 more Smart Citation
“…After standardization, however, only the expected shortfall of the German market portfolio remains higher than that of its UMD counterpart. Overall, our statistics presented here are consistent with those reported by Daniel and Moskowitz (2014) and Kadan and Liu (2014), who also found that momentum tends to suffer from severe left-tail risks.…”
Section: Summary Statistics: First and Secondsupporting
confidence: 92%
“…Eun, Huang, and Lai (2008) and Eun et al (2010) studied the benefits of holding internationally diversified style portfolios but did not examine how such portfolios perform during extreme periods. Both Daniel and Moskowitz (2014) and Kadan and Liu (2014) showed that momentum exhibits significant left-tail risks but did not examine whether these risks can be diversified internationally. Asness, Moskowitz, and Pedersen (2013) and asset classes.…”
mentioning
confidence: 99%
“…The second approach is based on recent work by Kadan and Liu (), who show how to evaluate investment performance in a way that accounts for higher moments by using the generalized risk measures of Aumann and Serrano () and Foster and Hart (). The performance indexes they construct, PAS and PFH, are the solutions to E[expfalse(PAS(1+R)false)]=1and E[logfalse(1+PFH(1+R)false)]=0.As with the other statistics in the table, we estimate them using the generalized method of moments (GMM).…”
Section: Risk and Risk Aversionmentioning
confidence: 99%
“…CE (gamma = γ ) refers to the certainty-equivalent rate for a CRRA investor with a risk aversion of γ . P AS and P FH are the performance indices of Kadan and Liu (2014) using the risk measures of Aumann and Serrano (2008) kurtosis of the hedged call portfolio, but they nevertheless raise the possibility of a relation between risk and return. 16 When we undertake the kind of risk adjustment that would be appropriate in a Gaussian setting or for investors with mean-variance preferences, we see that the greater risks associated with nontrading returns have little effect on the relative attractiveness of writing options over nontrading rather than trading periods.…”
Section: Risk and Risk-adjusted Performancementioning
confidence: 99%
“…A similar exercise was conducted inKadan and Liu (2014) in order to benchmark their newly proposed performance measure.…”
mentioning
confidence: 99%